THE IMPACT OF USING SHOPEE E-COMMERCE ON CONSUMER BEHAVIOR CASE STUDY IN PENAGAN VILLAGE, WEST MENDO SUB-DISTRICT, BANGKA DISTRICT - Sutrimono, Sutrimono; Masitoh, Siti; Sigalingging, Andy Sahat Maasi (Gema Kampus IISIP YAPIS Biak, 2025)
This study aims to analyze the impact of using Shopee e-commerce on consumer behavior in Penagan Village, West Mendo District, Bangka Regency. The development of digital technology and increasingly widespread internet access has encouraged rural communities to utilize e-commerce platforms such as Shopee in meeting their daily needs. The research method used is qualitative with a case study approach. The results showed that the use of Shopee has changed consumer behavior in terms of shopping habits, product preferences, and purchasing decision-making patterns. Consumers tend to prioritize convenience, competitive prices, and the variety of products offered through the platform. This study concludes that Shopee has a significant impact on consumer behavior in Penagan Village, with positive implications in increasing product accessibility, but also raises new challenges that need to be overcome. The findings are expected to be taken into consideration by businesses and the government in optimizing the benefits of e-commerce for rural communities.